2021
DOI: 10.1016/j.clinph.2020.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Motor dysfunction in mild cognitive impairment as tested by kinematic analysis and transcranial magnetic stimulation

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 74 publications
0
35
0
Order By: Relevance
“…Out of a total of 20,136 studies, 20,088 were removed according to the exclusion criteria and, additionally, if they (a) assessed visuomotor abilities in patients with MCI in Parkinson's Disease (MCI-PD) because of the major motor impairment or (b) provided information about upper extremity functioning by self-report measures. The final set, therefore, consisted of 48 studies assessing the following issues: 16 studies assessed VSWM abilities [17,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], 12 studies assessed anosognosia for memory deficits [40][41][42][43][44][45][46][47][48][49][50][51], 14 studies assessed visuomotor abilities [52][53][54][55][56][57][58][59][60][61][62][63][64][65], 2 studies investigated the relationship between VSWM and conversion [37,66], and 4 studies investigated the relationship between anosognosia for memory deficit...…”
Section: Data Extraction Results and Synthesismentioning
confidence: 99%
“…Out of a total of 20,136 studies, 20,088 were removed according to the exclusion criteria and, additionally, if they (a) assessed visuomotor abilities in patients with MCI in Parkinson's Disease (MCI-PD) because of the major motor impairment or (b) provided information about upper extremity functioning by self-report measures. The final set, therefore, consisted of 48 studies assessing the following issues: 16 studies assessed VSWM abilities [17,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], 12 studies assessed anosognosia for memory deficits [40][41][42][43][44][45][46][47][48][49][50][51], 14 studies assessed visuomotor abilities [52][53][54][55][56][57][58][59][60][61][62][63][64][65], 2 studies investigated the relationship between VSWM and conversion [37,66], and 4 studies investigated the relationship between anosognosia for memory deficit...…”
Section: Data Extraction Results and Synthesismentioning
confidence: 99%
“…Neurophysiological investigations in patients with generalized dystonia and FHD have variably shown that movement preparation can be abnormally prolonged [52][53][54][55][56][57][58][59][60]63,67,69]. Kinematic and electromyographic (EMG) recordings have demonstrated that in comparison with healthy subjects, patients performed single and multijoint arm movements with slower velocity and reduced amplitude, with co-contraction of agonist and antagonist muscles [21,65,70] or reduced contraction of muscle activity [66,71].…”
Section: B R Adykine S Ia In Hyperkine Tic Movement Disorder S Dystoniamentioning
confidence: 99%
“…Unlike PD, the clinical and neurophysiological features of bradykinesia in non‐parkinsonian conditions are poorly detailed. In some circumstances, the term bradykinesia has been used to indicate movement slowness, whereas in others it has been used to indicate reduced movement amplitude, and only a few studies have specifically investigated the presence of sequence effect in non‐parkinsonian conditions [6,50,54,55]. Also, the pathophysiology of bradykinesia in non‐parkinsonian conditions has never been comprehensively addressed, and it is unknown whether the same network involved in bradykinesia in PD is also involved in these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, studies have reported slower gait speed, as well as a shorter and more variable stride [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. Balance and postural control are also impaired [ 77 , 78 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ], and kinematic studies investigating handwriting and finger-tapping movements have reported fine motor control deterioration in MCI and AD patients [ 96 , 97 , 98 , 99 , 100 ].…”
Section: Motor Function Studies In Pathological Aging: Alzheimer’smentioning
confidence: 99%